Evaluation of Pre-Service English Teachers’ Integration of Educational Technology into their Lesson Plans - Wahyuni, Sri (Universitas Negeri Semarang, 2018)
The emergence of technology has shifted so many aspects of people‘ lives including but not limited to the way they interact with each other and accomplish almost all activities. In education context, use of technology has impacted teachers and students‘ interactions both in and outside classroom. For decades now, there has been research on technology use and its‘ benefits on teachers‘ instructional practices and students‘ learning. However, a study specifically looking at the integration of technology into teachers‘ lesson plans is still under research. Therefore, the paper was an attempt to investigate how pre-service English teachers integrated technology in the preparation stage of the instructional activities. The study focused on the evaluation of 22pre-service English teachers‘ lesson plans. It employed a qualitative approach with a document review method. It revealed that the pre-service English teachers have incorporate deducational technology including mobile devices and digital recording. Besides, the most frequently and commonly digital media used were Power Points, audios, videos and online resources downloaded from YouTube. In addition, they made use of communication and collaborative resource such as blogs. Finally, implication for further research is presented